The Character of the Peshitta Version of Ruth. Issue 2 (August 2019) - Tully, Eric J.
The mediating interference left by the translator of the Peshitta is an important source of information for the history of interpretation and for textual criticism. This study, based on terminology and methodology from the discipline of translation studies, is a comprehensive description of the translator's tendencies in the book of Ruth. The study concludes with a discussion of potential textual variants preserved in the Peshitta and an overall characterization of the translation.